Case Report: Giant hydropic leiomyoma of the uterus presenting as an aggressive abdominopelvic tumor - Giannios, Konstantinos; Anestiadou, Elissavet; Liampou, Eftychia; Spilioti, Lydia Konstantina; Bakaloudi, Dimitra Rafailia; Papadopoulos, Vasileios (Frontiers in Oncology, 2025)
Hydropic leiomyoma (HLM) is a rare subtype of uterine leiomyoma characterized by significant interstitial fluid accumulation, often mimicking malignant tumors due to its imaging features. Although most uterine leiomyomas are benign and commonly occur in women of reproductive age, HLM can grow to an unusually large size, leading to diagnostic challenges. In this case report, we present a case of a 59-year-old postmenopausal woman with a giant HLM exhibiting extensive cystic hydropic degeneration resembling an aggressive abdominopelvic tumor. The tumor measured 35 × 27 × 17 cm and caused a significant mass effect on surrounding organs. Surgical management involved a total abdominal hysterectomy with right salpingo-oophorectomy via midline laparotomy. Intraoperative findings included displacement of the small bowel, transverse colon, and greater omentum by the tumor, with adherence of the left adnexa to the external surface of the uterus. A left ureteral transection occurred during tumor dissection and was successfully repaired with ureteral reanastomosis and placement of a pigtail stent. The operation lasted 4 hours 11 minutes, and the patient had an uncomplicated postoperative recovery. Histopathological examination confirmed the diagnosis of HLM with extensive cystic degeneration. Based on available literature, this case appears to represent the largest HLM reported to date, highlighting the importance of accurately distinguishing benign from malignant tumors to guide appropriate clinical management. This case underscores the complexities associated with diagnosing and surgically treating large, degenerating uterine leiomyomas.